Automated human cortical bone Haversian canal histomorphometric comparison system - Abdullah, Hadi; Abdul Jamil, Muhammad Mahadi; Khan, Ijaz; Abd Wahab, Mohd Helmy Bin; Mohd Nor, Faridah (Elsevier Ltd., 2020)
This research presents comparison of histological parameters of cortical bones for Malaysian population. For this research 44 samples were collected from Department of Pathology, Faculty of Medicine Universiti Kebangsaan Malaysia. Sample preparation being one of the important aspects of this research, is described in detail. Six Haversian canal-based parameters were selected for the comparison. Sex and race comparisons were performed on the collected Malaysian samples. Race comparison was performed between the two Malaysian races (Chinese-Indian). The results obtained from sex comparison demonstrates difference in mean Haversian canal area (hcm). The hcm parameter in female samples were found to be significantly larger than male samples (P < .05). This research also presents an automated system which can be used as a platform to perform Haversian canal parameter comparison. The system is designed to automatically check normality of the parameters measurement data and select the relevant comparison test. It is divided into two main section. The first section provides race comparison platform while the second section is dedicated for sex comparison.